OVERVIEW OF LEGAL MONITORING ISSUES IN THE RUSSIAN FEDERATION - Kutjko, Viktorija; Rudakov, Nikita (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The category of "legal monitoring" is analyzed in the context of universal methods, means, ways of studying and monitoring the parameters of current legislation and analyzing the information obtained during periodic research. The definition of legal monitoring is given as a planned activity for systematic collection of information on existing legislation according to predetermined criteria, for its study, which uses different methods of scientific knowledge, as well as for assessment of information and conclusions derived from it, on the state and development of legislation (or of its parts) under the influence of various factors. One of the criteria for assessing the results of legislative activity is the functioning of the law after its adoption. The constant increase in the number of legal acts, contradictions in the legislation, and the poor technical condition of the legislation are listed as problems in the application of legal monitoring. Monitoring of legislation, with the use of universal methods and means, enables the study and monitoring of the parameters of existing legislation and the analysis of information obtained during a series of periodically repeated studies.
Keywords: legal monitoring; legislation; Russia; Russian Federation